2017
DOI: 10.1161/jaha.117.006376
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Reoperation After Acute Type A Aortic Dissection: Implications for Index Repair Strategy

Abstract: BackgroundThe optimal surgical approach for management of acute type A aortic dissection remains controversial. This study aimed to assess outcomes of reoperation after acute type A dissection repair to help guide decision making around index operative strategy.Methods and ResultsAll aortic reoperations (n=129) at a single referral institution from August 2005 to April 2016 after prior acute type A dissection repair were reviewed. The primary outcome was 30‐day or in‐hospital mortality. Secondary outcomes incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 21 publications
2
30
0
1
Order By: Relevance
“…Other studies have shown freedom from reoperation of 82-94% at five years [85,101,102]. However, Wang et al found that patients with connective tissue disease had a 45% risk of reoperation at a median follow-up time of 2.5 years and Pan et al found that patients with connective tissue disease had a five times higher risk of proximal reoperation [8,103]. This possibly indicates that a more aggressive primary approach may be feasible in patients with hereditary conditions.…”
Section: Complicationsmentioning
confidence: 99%
“…Other studies have shown freedom from reoperation of 82-94% at five years [85,101,102]. However, Wang et al found that patients with connective tissue disease had a 45% risk of reoperation at a median follow-up time of 2.5 years and Pan et al found that patients with connective tissue disease had a five times higher risk of proximal reoperation [8,103]. This possibly indicates that a more aggressive primary approach may be feasible in patients with hereditary conditions.…”
Section: Complicationsmentioning
confidence: 99%
“…Data on this more aggressive approach, such as that from the German Registry for Acute Aortic Dissection type A (GERAADA), demonstrates higher early mortality and morbidity with index total arch as compared to hemi-arch replacement, and therefore the appropriateness of this more aggressive approach requires further study. Data from our institution on outcomes of aortic reoperation after prior acute type A dissection repair demonstrates that the majority (83%) of such cases are elective and can be performed with low rates of operative mortality (6%) and organspecific morbidity [5]. These data provide support for limited index repair for acute type A dissection, especially for patients undergoing repair in lower volume centers without expertise in extensive repair.…”
Section: ○Gchad Hughesmentioning
confidence: 72%
“…However, for patients that have undergone one re-intervention, the rate of re-re-interventions is as high as 40% at 5 years, and is especially so for patients with connective tissue disorders. 24 Among a recent group of large studies, 81À92% of re-intervention cases were elective, 5,13,24,25 perhaps contributing to a very low re-operative risk, which ranged from 0% to 12% (weighted average 4.7%) 1,3,5,7,11,13,22À24,26 Thus, in terms of the magnitude of the downstream problem: re-interventions are mostly elective, infrequent, low-risk events.…”
Section: How Big Is the Downstream Problem: How Many Come Back How Umentioning
confidence: 99%